Why do preconception and pregnancy lifestyle interventions show little evidence of success in preventing overweight and obesity in children? A scoping review. (March 2023) - Philippe, Kaat; Teo, Shevaun; Perrotta, Carla; McAuliffe, Fionnuala M; Phillips, Catherine M
Abstract: Background: Adverse lifestyle factors in the periconception and early life period, including high maternal prepregnancy BMI and excessive gestational weight gain, are important risk factors for childhood obesity. Early prevention is key, but results from systematic reviews of preconception and pregnancy lifestyle interventions have shown mixed success in improving children's weight outcomes and adiposity. We aimed to investigate the complexity of these early interventions and process evaluation components and authors' statements to improve our understanding regarding their limited success. Methods: We did a scoping review, guided by frameworks of the Joanna Briggs Institute and Arksey and O'Malley. Eligible articles (with no language restriction) were identified between July 11 and Sept 12, 2022, by searching PubMed, Embase, and CENTRAL; consulting previous reviews; and conducting CLUSTER searches. A thematic analysis was conducted with NVivo in which process evaluation components and authors' interpretations were coded as reasons. Intervention complexity was evaluated with the Complexity Assessment Tool for Systematic Reviews. Findings: 40 publications corresponding to 27 eligible preconception or pregnancy lifestyle trials with child data beyond age 1 month were included. Most interventions started during pregnancy (n=25) and focused on multiple lifestyle factors (eg, diet and exercise). The preliminary results show that almost no interventions involved the participants' partner or social network. Potential reasons for limited success in the interventions preventing overweight or obesity in children included the start time of the intervention, duration and intensity, and sample size or dropout rates. The results will be discussed with an expert group as part of a consultation stage. Interpretation: The results and discussions with an expert group are expected to uncover gaps and inform the design or adaptation of future interventions and approaches to potentially increase success rates in preventing childhood obesity. Funding: Funded by the Irish Health Research Board through the transnational JPI HDHL ERA-NET HDHL-INTIMIC-2020 call (PREPHOBES): EU Cofund action (number 727565; EndObesity project).